(untitled) - Vitale, Joe (Hoboken, N.J., 2007)
The principles are sound and sensible and guaranteed to help any businessperson make more money. Since 99.9 percent of businesses don't use them, anyone putting the seven lost secrets to work will gain an unbelievable edge over the competition.
Keywords: Advertising,Success in business,Consumer satisfaction,Social responsibility of business,Quảng cáo,Thành công trong kinh doanh,Sự hài lòng của người tiêu dùng,Trách nhiệm xã hội của doanh nghiệp; Psychological aspects,Khía cạnh tâm lý